Novel conductive nanocomposites from perfluoropolyether waterborne polyurethanes and carbon nanotubes. (17th June 2014) - Molina, Diego; Griffini, Gianmarco; Levi, Marinella; Turri, Stefano
<x xml:space="preserve">Abstract</x> The exceptional electrical conductivity of carbon nanotubes (CNTs) has been exploited for the preparation of conductive nanocomposites based on a large variety of insulating polymers. Among these, perfluoropolyether‐polyurethanes (PFPE‐PUs) represent a class of highly performing fluorinated materials with excellent water/oil repellency, chemical resistance, and substrate adhesion. The incorporation of highly conductive fillers to this class of highly performing materials allows them to be exploited in new technological and industrial fields where their unique properties need to be combined with the electrical conductivity or the electrostatic dissipation properties of carbon nanotubes. However, no studies have been presented so far on nanocomposites based on PFPE‐PUs and CNTs. In this work, polymer nanocomposites based on waterborne PFPE‐PUs and increasing amounts of carboxylated multiwall CNTs (COOH‐CNTs) were prepared and characterized for the first time. The effect of increasing concentration of COOH‐CNTs on the physical, mechanical, and surface properties of the nanocomposites was investigated by means of rheological measurements, dynamic mechanical analysis, thermal characterization, optical contact angle measurements, and scanning electron microscopy. In addition, electrical measurements showed that the highly insulating undoped PFPE‐PU system undergoes substantial modifications upon addition of COOH‐CNTs, leading to the formation of conductive nanocomposites with electrical conductivities as high as 1 S/cm. The results of this study demonstrate that the addition of COOH‐CNTs to PFPE‐PU systems represents a promising strategy to expand their possible use to technological applications where chemical stability, water/oil repellence and electrical conductivity are simultaneously required. Copyright © 2014 John Wiley & Sons, Ltd.